2022
DOI: 10.1039/d2ma00568a
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled silk fibroin hydrogels: from preparation to biomedical applications

Abstract: Silk fibroin (SF) from Bombyx mori silkworm has been used as a textile fiber for centuries. In addition, for decades, SF has been used as a suture material. SF's unique...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 186 publications
0
17
0
Order By: Relevance
“…It was observed that the half-life of the SF solution could be increased from 3 weeks to more than 6 months if the solution is stored at 4 • C without removing LiBr. Removal of LiBr could allow the interchain hydrophobic interactions between the SF molecules and lead to the formation of hydrogen-bonded βsheets, which eventually convert the solution to gel and finally solid form [56,57]. The presence of LiBr in the SF solution was also crucial for the successful methacrylation of SF because the agitation during the reaction without LiBr may result in the shear-induced unfolding of the SF molecules.…”
Section: Extraction Of Sf Fibers and Preparation Of Sf Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the half-life of the SF solution could be increased from 3 weeks to more than 6 months if the solution is stored at 4 • C without removing LiBr. Removal of LiBr could allow the interchain hydrophobic interactions between the SF molecules and lead to the formation of hydrogen-bonded βsheets, which eventually convert the solution to gel and finally solid form [56,57]. The presence of LiBr in the SF solution was also crucial for the successful methacrylation of SF because the agitation during the reaction without LiBr may result in the shear-induced unfolding of the SF molecules.…”
Section: Extraction Of Sf Fibers and Preparation Of Sf Solutionmentioning
confidence: 99%
“…The presence of LiBr in the SF solution was also crucial for the successful methacrylation of SF because the agitation during the reaction without LiBr may result in the shear-induced unfolding of the SF molecules. The increased exposure of the hydrophobic domains and hence the formation of β-sheet clusters can eventually lead to physical entanglement of fibroin fibers resulting in aggregation and gelation of SF [56,57].…”
Section: Extraction Of Sf Fibers and Preparation Of Sf Solutionmentioning
confidence: 99%
“…8 Polymeric hydrogels are 3D arrangements of polymers that absorb water due to their hydrophilic nature, making them suitable for interacting with human tissues. [9][10][11] The development and design of stimuli-responsive hydrogels for DDSs have gained considerable attention in recent years. Stimuli-responsive DDSs are innovative platforms designed to release therapeutic agents in response to specific stimuli, ensuring precise control over drug release at targeted sites within the body.…”
Section: Introductionmentioning
confidence: 99%
“…Several strategies have been adopted, including but not limited to freeze-drying [ 11 , 12 , 13 ], salt-leaching [ 11 , 14 , 15 ], and foaming [ 16 , 17 , 18 ]. In almost all of them, mechanical stability is ensured by the folding of the secondary structure into β-sheets in a mechanism that is known as physical cross-linking [ 19 , 20 , 21 , 22 ]. Just a single method was reported that is based on the chemical cross-linking of a methacrylated silk fibroin (methacrylated silk, Sil-MA) [ 16 , 23 ].…”
Section: Introductionmentioning
confidence: 99%